Growth performance, carcass characteristics and meat quality of Northern Finncattle steers compared to Holstein steers offered grass silage-grain-based ration - Keto, Liisa; Manni, Katariina; Tuomivaara, Anne; Soppela, Päivi; Huuskonen, Arto (Wiley, 2024)
Background: Finnish beef production is largely based on dairy breeds. Eastern Finncattle, Western Finncattle, and Northern Finncattle (NFC) are native breeds, whereas Holstein (HO) and Nordic Red are the most important commercial dairy breeds. The NFC has been the closest to extinction among Finnish native cattle breeds. The objective of the experiment was to provide data on meat quality of NFC compared to HO. To our knowledge no previously published scientific data about the meat quality traits of NFC is available. Results: The targeted slaughter age was 600 days for both NFC and HO. The carcass gain of the HO steers was 60% higher compared to NFC steers. No breed differences in dressing proportion, carcass conformation, or carcass fat score were observed. Breed had no effect on the pH, color, drip loss, chemical composition, shear force value, or sensory tenderness of the longissimus lumborum muscle. However, beef flavor of the NFC steers was evaluated 7% better compared to the HO steers. In addition, the longissimus lumborum muscle of the NFC steers tended to be juicier than that of the HO steers. Conclusions: Only little variability in meat quality traits was observed between the breeds. However, NFC requires a longer growing period than HO when targeting the same carcass weight. To promote the use of the NFC in beef production, it is necessary to find other than economic production efficiency features, which would provide added value for premium meat quality to compensate the lower production efficiency.
Keywords: beef production; beef quality; eating quality; gain; native breed